Peran Pemerintah dan Masyarakat dalam Menjaga Kestabilan Harga Pangan yang Kian Meningkat - Febriansyah (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2024)
Law in Indonesia not only discusses criminal, political, socio-cultural and constitutional issues but also discusses the economy because the economy, markets, prices, basic goods cannot be separated from the intervention of the government itself, in recent times the price of basic necessities has increased and the government is still trying to make efforts to prevent inflation in the price of food goods. In this writing the author uses a library research method in which the data sources obtained come from books, previous journals and articles, besides that the author also uses qualitative research methods in which the author also conducts interviews to obtain information which is then concluded into a scientific paper. And based on this, the author has formulated several problem formulations including (1) what is the cause of the increase in food prices getting higher in recent months, (2) what is the role of the government in maintaining food price stability so that it does not continue to rise, (3) what is the role of the community in maintaining price stability. And the conclusions of this journal writing are (1) there are four factors that affect the increase in staple food prices including a. The foreign price situation and the dollar exchange rate related to commodity supplies that depend on imports, b. Unstable climatic conditions, c. Distribution that is not smooth and d. Speculation factors, (2) the role of the government in maintaining food price stability. Speculation factors, (2) the role of the government in maintaining the stability of food prices include a. The government conducts cheap market operations, b. Supervise and maintain stocks of goods so that they are not limited or reduced, c. Monitor so that there is no hoarding of food goods, d. The local government distributes bulog rice to the local government. The local government distributes Bulog rice to the community, e. The government will also continue to carry out market operations and strengthen the smooth distribution of supplies, f. The government issued a special fiscal policy for the distribution of Bulog rice to the community. The government issues special fiscal policies for exports and imports. (3) and the community also plays a role in reducing inflation and stabilizing food prices, including by doing a. The community is expected to shop according to their needs, b. The community can compare good and cheap prices, c. Shop with substitute goods if they feel the goods are expensive, d. Not hoarding goods that can cause inflation. Not hoarding goods that can cause scarcity and if caught hoarding goods will be subject to sanctions and penalties that have been regulated by the government.